2015
DOI: 10.1186/s12866-015-0515-4
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of bacteriocin gene clusters in the gastrointestinal tract, based on the Human Microbiome Project’s reference genome database

Abstract: BackgroundThe human gut microbiota comprises approximately 100 trillion microbial cells which significantly impact many aspects of human physiology - including metabolism, nutrient absorption and immune function. Disturbances in this population have been implicated in many conditions and diseases, including obesity, type-2 diabetes and inflammatory bowel disease. This suggests that targeted manipulation or shaping of the gut microbiota, by bacteriocins and other antimicrobials, has potential as a therapeutic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 76 publications
(74 reference statements)
4
92
0
1
Order By: Relevance
“…An in silico study of the genomes of gut bacteria from the Human Microbiome Project identified lantibiotic-associated genes from a range of genera, including R. obeum A2-162 [33]. Other Clostridiales have been shown to produce the bacteriocins albusin B, a type III bacteriocin [57], and the lantibiotics ruminococcin A and ruminococcin C [58,59], but these were not found to have any sequence similarities to the nisin O cluster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in silico study of the genomes of gut bacteria from the Human Microbiome Project identified lantibiotic-associated genes from a range of genera, including R. obeum A2-162 [33]. Other Clostridiales have been shown to produce the bacteriocins albusin B, a type III bacteriocin [57], and the lantibiotics ruminococcin A and ruminococcin C [58,59], but these were not found to have any sequence similarities to the nisin O cluster.…”
Section: Discussionmentioning
confidence: 99%
“…It is a rich potential source of novel antimicrobials that have evolved to function in the challenging conditions of the gastrointestinal tract, and recent research suggests that bacteriocin production is widespread [32,33]. Using genome mining of human gut bacteria, new lantibiotic sequences sharing considerable amino acid sequence homology with class AI lantibiotics, and especially nisin U, were discovered from anaerobic bacterium Blautia obeum A2-162.…”
Section: Introductionmentioning
confidence: 99%
“…A producer cell encodes both toxic and immunity functions, killing neighbouring cells while protecting itself and its progeny from the effects of the bacteriocin. Recent studies have used metagenomics to identify bacteriocins [103,104], shown potential fitness advantages of producers in vivo [105], and observed protective effects of producers against pathogens [106,107]. As these molecules seem to play a role in modulating microbial populations within a host, they may prove useful tools for subtractive-type therapies.…”
Section: Efforts To Harness and Engineer The Microbiotamentioning
confidence: 99%
“…The bacteriocin pyocin S5 from P. aeruginosa PAO1 has been engineered to eradicate Pseudomonas species phylogenetically close to PAO1 [66], and hence is a prospective therapeutic for treating Pseudomonas infections. Recently, many bacteriocins have been identified from the gut microbiota [67,68]. For example, thuricin CD, which has a narrow spectrum, is effective in killing C. difficile without significant impact on the microbiota composition in a distal colon model [69], while the bacteriocin Abp118 produced in Lactobacillus salivarius UCC118 is found to be directly responsible for significantly protecting mice against Listeria monocytogenes infection [70].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%